Counseling Services with A Behavioral Approach To Student Moral and Ethics Instrument at SDN 1 Tembilahan City - Nisya, Wirdatun; Netrawati, Netrawati; Ardi, Zadrian (Universitas Trunojoyo Madura, 2023)
Instilling morals and ethics in students is important to do so that they develop optimally. Instilling morals and ethics can be done in various ways, one of which is by providing guidance and counseling services with a behavior approach . The purpose of this study was to find out the methods used by counseling with the Behavioral approach in instilling morals and ethics in students. The method used is descriptive qualitative. The subjects of this study were teachers and students at SDN 1 Tembilahan City. Data collection techniques by observing, interviewing and documentation. Data analysis techniques use the presentation, reduction and verification of data. The results of this study are the inculcation of morals and ethics through counseling services with a Behavioral approach by introducing and teaching mutual assistance between others, teaching how to control emotions, and providing habituation to comply with existing rules at school